The State of Food and Agriculture (2016) 2015: Social protection and agriculture - Vos, Rob (2016)
Presentation by Rob Vos, Director for Agricultural Development Economics (ESA) at the Food and Agriculture Organization of the United Nations (FAO) February 2, 2016 Washington, DC